BOOK REVIEW: DIVIDED: WHY WE'RE LIVING IN AN AGE OF WALLS (Margalla Papers, 2023)
Divided is all about creating walls, their perceived necessity and their impact. Deep divisions based on wealth, race, religion and politics are the reasons behind barriers preventing violence and maintaining defence. Tim Marshall stated that in this world, there have always been boundaries, ranging from small scale to larger ones. Physical boundaries are mostly demarcated on maps and the ground, and movement through them is restricted. Barriers at every level create a 'US' vs 'THEM' mentality and are somehow crucial for the promotion of national identity. Thousands of miles of walls and fences have been built worldwide in the twenty-first century. The growing higher walls and barriers are reshaping the world. The author has discussed barriers in China, the US, Israel-Palestine, the Middle East, the Subcontinent, Africa, Europe and the UK.